2020
DOI: 10.1001/jamaoncol.2020.3927
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and Safety of nab-Paclitaxel vs Paclitaxel on Survival in Patients With Platinum-Refractory Metastatic Urothelial Cancer

Abstract: IMPORTANCETreatment options for platinum-refractory metastatic urothelial cancer (mUC) are limited, and outcomes remain poor. Nab-paclitaxel is an albumin-bound formulation of paclitaxel showing promising activity and tolerability in a prior single-arm trial.OBJECTIVES To evaluate the efficacy and safety of nab-paclitaxel vs paclitaxel in platinum-refractory mUC. DESIGN, SETTING, AND PARTICIPANTSIn this investigator-initiated, open-label, phase 2 randomized clinical trial conducted across Canada and Australia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…In this study, nab-paclitaxel showed higher rates of all-cause grade 3e4 toxicities, including peripheral sensory neuropathy (all grades peripheral neuropathy was 74% for nab-paclitaxel versus 66% paclitaxel; grade 3e4 was 7% versus 3%). 14 Therefore, the main result of the PEANUT trial at this point is that taxanebased chemotherapy may still be a valid option for combination with checkpoint blockade, and using standard paclitaxel as a backbone therapy could result in an even better tolerated combination. Our chemoimmunotherapy combination was noteworthy in less pretreated patients with good prognostic factors, whereas combinations of immunotherapeutic agents or EV yield the potential to rescue an additional proportion of patients we were unable to rescue in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, nab-paclitaxel showed higher rates of all-cause grade 3e4 toxicities, including peripheral sensory neuropathy (all grades peripheral neuropathy was 74% for nab-paclitaxel versus 66% paclitaxel; grade 3e4 was 7% versus 3%). 14 Therefore, the main result of the PEANUT trial at this point is that taxanebased chemotherapy may still be a valid option for combination with checkpoint blockade, and using standard paclitaxel as a backbone therapy could result in an even better tolerated combination. Our chemoimmunotherapy combination was noteworthy in less pretreated patients with good prognostic factors, whereas combinations of immunotherapeutic agents or EV yield the potential to rescue an additional proportion of patients we were unable to rescue in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Nine trials (75%) were evaluated in breast cancer, 1 (8.3%) in NSCLC, 1 (8.3%) in urothelial cancer, and 1 (8.3%) in gastric cancer. 7,[20][21][22][23][24][25][26][27][28][29][30][31] Most trials investigated nab-paclitaxel as a single agent; however, 2 trials combined nab-paclitaxel with other agents (bevacizumab and carboplatin). There were 4 trials investigating nab-paclitaxel monotherapy in different doses, whereas the other 6 trials investigated a single dose.…”
Section: Resultsmentioning
confidence: 99%
“…There are, however, two randomized trials worthy of attention: a phase III study, comparing vinflunine to best supportive care (BSC) alone, 60 and a phase II trial, comparing paclitaxel to nab-paclitaxel. 62 …”
Section: Subsequent Lines Of Therapymentioning
confidence: 99%
“…Paclitaxel is a well-known and safe drug and is relatively inexpensive, with RRs observed in a quarter of the patients; it therefore remains a potential option in further lines of treatment. 62 In jurisdictions without access to novel therapies, paclitaxel remains a viable option in the post-platinum setting, with RRs at least similar to that seen with second line immunotherapy.…”
Section: Subsequent Lines Of Therapymentioning
confidence: 99%
See 1 more Smart Citation